Electronic structure of the surface-superconducting Weyl semimetal PtBi 2 - Vocaturo, Riccardo (2024)
Trigonal PtBi2 is a layered semimetal without inversion symmetry, featuring 12 Weyl points in the vicinity of the Fermi energy. Its topological Fermi arcs were recently shown to superconduct at low temperatures where bulk superconductivity is absent. Here, we perform first-principles calculations to investigate in detail the bulk and surface electronic structure of PtBi2, and obtain the spin texture as well as the momentum-dependent localization of the arcs. Motivated by the experimentally observed recovery of inversion symmetry under pressure or upon doping, we interpolate between the two structures and determine the energy and momentum dependence of the Weyl nodes. For deeper insights into the surface superconductivity of PtBi2, we construct a symmetry-adapted effective four-band model that accurately reproduces the Weyl points of PtBi2. We supplement this model with an analysis of the symmetry-allowed pairings between the Fermi arcs, which naturally mix spin-singlet and spin-triplet channels. Moreover, the presence of surface-only superconductivity facilitates an intrinsic superconductor-semimetal-superconductor Josephson junction, with the semimetallic phase sandwiched between the two superconducting surfaces. For a phase difference of , zero-energy Andreev bound states develop between the two terminations.